The Theory of P. Ya. Galperin in research in Mathematics Education - Gonçalves, Paulo Gonçalo Farias; Núñez, Isauro Beltrán (Educação Matemática Debate, 2017)
Since its inception, Mathematics Education has been consolidating itself as a research area. Given its multifaceted nature, State of the Art studies are important to point out trends and gaps in its investigative lines. Thus, this article aims to map and characterize works under the contribution of Galperin's Theory available in two digital libraries. Being a State of the Art research, we selected 15 studies and categorized them according to: course, institution, levels and modalities of teaching and content addressed. We verified in the investigations: the prevalence in professional masters, distribution in all Brazilian regions, from Elementary Education to Higher Education and in the modalities Special Education and Distance Education, Dealing with all subareas of Basic Mathematics. Thus, it is fundamental that new research on Galperin's Theory be undertaken, aiming to contribute to the diffusion of a school education perspective aimed at the integral development of students.